Factors affecting the in vitro performance of dentin-bonding systems - Masashi Miyazaki; Keishi Tsubota; Toshiki Takamizawa; Hiroyasu Kurokawa; Akitomo Rikuta; Susumu Ando (Elsevier, 2012)
This paper reviews the performance of current adhesive systems in tests of bond strength between resin composites and tooth structures. The longevity and success of resin composite restorations depend upon the adhesive systems providing durable bonds with tooth substances. Both in vitro and in vivo testing has been used to predict the clinical outcome of treatments with adhesive materials. Subtle variations in sample preparation can severely affect the bond strength, regardless of the test method employed. In addition to the large range of factors that affect bond strength, various load applications have been used to quantify the adhesion between composites and tooth structures. Dentin bond strength is normally evaluated by conducting mechanical tests in the tensile and/or shear mode, but the crosshead speeds used vary over a relatively wide range in the published literature. This review provides an overview of the current characterization of dental adhesives and the factors affecting their performance in bond-strength tests.